Real Subsumption of Labor Under Capital and Dispossession Practices. Questions to Michael Hardt. - Juskowiak, Piotr (Praktyka Teoretyczna, 2015)
Real Subsumption of Labor Under Capital and Dispossession Practices. Questions to Michael Hardt.